2016
DOI: 10.1093/femsec/fiw065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of full-scale advanced water treatment on antibiotic resistance genes in the Yangtze Delta area in China

Abstract: As emerging microbial contaminants, antibiotic resistance genes (ARGs) are widespread in the aquatic environment, including source water, which might enter water supply systems and endanger public health by enhancing the resistance of opportunistic pathogens to some antibiotics. In the present study, we investigated how water treatments affect the levels of ARGs in a full-scale drinking water treatment plant for one year using real-time PCR. The 16s rRNA gene and eleven ARG families, including tetA, tetG, aacC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 61 publications
4
15
0
Order By: Relevance
“…As a result, from 112 to 122 genes were found in tap water samples, depicting the diversity of ARGs in this medium [17]. The elevated level of ARGs in tap water, in comparison to treated water, was confirmed also by Zhang et al [51].…”
Section: Args Occurring In Arb and Dna Isolated From Tap Watera Reviewsupporting
confidence: 69%
See 3 more Smart Citations
“…As a result, from 112 to 122 genes were found in tap water samples, depicting the diversity of ARGs in this medium [17]. The elevated level of ARGs in tap water, in comparison to treated water, was confirmed also by Zhang et al [51].…”
Section: Args Occurring In Arb and Dna Isolated From Tap Watera Reviewsupporting
confidence: 69%
“…In general, the DNA obtained by commercial kits was pure enough to perform PCR assay (the minimum A260/A280 ratios was 1.40) and solutions obtained by phenol/chloroform methods required further purification steps in some cases, what could hinder PCR investigations [55]. The alternative solution was implemented by Zhang et al, who combined the application of the commercial kit with further phenol-ethanol methods [51].…”
Section: Extraction Of Dna From Arb and Tap Water Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, this study found that, domestic use of tap water only as pre-admission history is protective factor (p = 0.040) for bacteremia. Treatment of water for domestic use by sand filtrations at water treatment plant in Mwanza [38], may have been played an effective role of reducing the absolute concentrations of MDR-bacteria and antibiotic resistance genes (ARGs) from contaminated source [39] as reported by Zhang et al, 2016 [40]. Thus, admitted neonates with parents' domestic use of water from open sources such as dams and lake, should be screened for possibilities of bacteremia due to GNB.…”
Section: Discussionmentioning
confidence: 99%